Knowledge Translation of Interprofessional Collaborative Patient-Centred Practice: The Working Together Project Experience - MacDonald, Colla; Archibald, Douglas; Stodel, Emma; Chambers, Larry; Hall, Pippa (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractThe Working Together (WT) project involved the design and delivery of an online learning resource for healthcare teams in long-term care (LTC) so that knowledge regarding interprofessional collaborative patient-centred practice (ICPCP) could be readily accessed and then transferred to the workplace. The purpose of this paper is to better understand the process of knowledge translation in continuing education for healthcare professionals by documenting our experiences using Lavis et al.’s (2003) organizing framework for knowledge transfer, and highlighting the impact this approach had on the design, development, delivery, and evaluation of the WT program. Fifty-nine pharmacists, physicians, nurses, and nurse practitioners from 17 LTC homes across Ontario, Canada participated in this project. The effectiveness of the knowledge translation of ICPCP through the WT project was evaluated using the Demand-Driven Learning Model (DDLM) evaluation tool (MacDonald, Breithaupt, Stodel, Farres, & Gabriel, 2002) to assess learners’ reactions to the learning resource. Data from quantitative pre-post surveys and qualitative interviews revealed that learners found using the WT online resource to be a satisfactory learning experience, obtained new knowledge and skills regarding ICPCP, transferred knowledge to the workplace, and reported that learning had a positive effect on the residents they cared for.